Metabolic and vascular imaging markers for investigating Alzheimer’s disease complicated by sleep fragmentation in mice - Han, Xiaoning; Liu, Guanshu; Lee, Sang Soo; Yang, Xiuli; Wu, Mark N.; Lu, Hanzhang; Wei, Zhiliang (Frontiers in Physiology, 2024)
Background: Sleep problem is a common complication of Alzheimer's disease (AD). Extensive preclinical studies have been performed to investigate the AD pathology. However, the pathophysiological consequence of AD complicated by sleep problem remains to be further determined. Purpose: To investigate brain metabolism and perfusion in an AD mouse model complicated by sleep problem, and subsequently identify potential imaging markers to better understand the associated pathophysiology.We examined the oxygen extraction fraction (OEF), cerebral metabolic rate of oxygen (CMRO2), and cerebral blood flow (CBF) using state-of-the-art MRI techniques in a cohort of 5xFAD model mice. Additionally, neuroinflammation, indicated by activated microglia, was assessed using histology techniques. Sleep fragmentation (SF) was utilized as a representative for sleep problems. Results: SF was associated with significant increases in OEF (P=0.023) and CMRO2 (P=0.029), indicating a state of hypermetabolism. CBF showed a significant genotype-by-sleep interaction effect (P=0.026), particularly in the deep brain regions such as the hippocampus and thalamus. Neuroinflammation was primarily driven by genotype rather than SF, especially in regions with significant interaction effect in CBF measurements. Conclusion: These results suggest that brain metabolism and perfusion measurements are promising markers for studying the co-pathogenesis of AD and SF.